Effectiveness of platysma muscle flap in preventing Frey syndrome and depressive deformities after parotidectomy. Issue 5 (May 2016) - Hayashi, Ayato; Mochizuki, Mariko; Suda, Shunichi; Natori, Yuhei; Ando, Erika; Yoshizawa, Hidekazu; Senda, Daiki; Tanaka, Rica; Mizuno, Hiroshi
Summary: Background: Frey syndrome (FS) or depressive deformity (DD) occurring after parotidectomy significantly reduces a patient's quality of life. However, there seems to be no effective treatment strategy against these complications. In this study, we report our experience of using platysma muscle flap (PMF) to prevent the development of FS and DD after parotidectomy, and evaluate its effect subjectively and objectively. Methods: Superficial parotidectomy was performed for eight cases of parotid gland tumor, and a PMF was transferred to cover the site. The incidence of FS and DD were evaluated subjectively, using a questionnaire to the patients and board-certified reconstructive surgeons, and objectively, using Minor's starch-iodine test. Results: In seven patients, the defect could be completely covered with PMF, and none of them developed FS or obvious DD. However, in one patient, the defect could be only partially covered, and the patient developed complications in the exact site that the flap did not cover. Overall scores from the questionnaire were high in relation to both cosmetic and functional perspectives from most of the patients and all the surgeons. No patients had major postoperative complications requiring revision. Conclusions: PMF can be useful to cover the defect and prevent complications after parotidectomy. PMF is relatively easy to perform with fewer complications; however, a complete coverage of the defect should be ensured to obtain optimal results.